SINTESIS BARIUM M-HEXAFERRITTE (BaFe12-xNixO19) DOPING LOGAM NIKEL DENGAN METODE KOPRESIPITASI - Munib -; Susilawati -; Lalu Rudyat Telly Savalas (Jurnal Penelitian Pendidikan IPA, 2016)
Synthesis of Barium M-Hexaferrite (BaFe12-xNixO19) nickel metal doping have been done with co-precipitation method and its effect on temperature changes and substitution dopants. Basic materials used in the synthesis of BaCO3, FeCl3.6H2O, HCl, NH4OH and nickel metal. The process of synthesis of barium M-heksaferit conducted at the Faculty of Mathematics and Natural Sciences Analytical Laboratories Unram. This study used a variation of calcination temperature of 80, 400, 600 and 800°C for 4 hours with a variety of dopants 0; 0.4; 0.7 and 0.9. Synthesis results show that changes in the concentration of the dopant variables and calcination temperature indicate a tendency to change color to brown-black powder.Abstract: Barium Mhexaferrite, dopant, nickel, co-precipitation.